The Capital Structure Determinants of Non-financial UK Listed Companies - Yin, Mohan (2013)
Since MM theory was mentioned in the last century, theories and empirical researches on capital structure and its influencing factors sprung up endlessly. In United Kingdom, the capital structure concerned issues are numerous. But the global financial crisis also brought unprecedented impacts to developed countries’ corporations. The researches on the firm’s capital structure determinants became the focus of attention experts from the global worlds. From the past few years, the experts continuously explore and conduct empirical analysis on this domain. From static model to dynamic adjustment model, from microeconomic factors to intermediate until macroeconomic factors, because of the differences among data chosen, research methods and measurement in respective levels, the experts draw diversified and even contrary conclusions. Due to particular economic and financial system in addition to unpredictable international economic environments, It’s of great importance to figure out the determinants on capital structure of non-financial listed companies in UK, carry out correct empirical analysis and optimize the debt-financing policy and capital structure of United Kingdom.